Preliminary Study of Chemical Bonding Learning Media Based on Podcast as Digital Entertainment Era 5.0 - Widarti Hayuni Retno; Wiyarsi Antuni; Yamtinah Sri; Shidiq Ari Syahidul; Sari Meyga Evi Ferama; Nuriyanti Dian; Wijaya Ginesia Dudin; Rokhim Deni Ainur (E3S Web of Conferences, 2024)
In the ever-evolving digital era, technology has changed the way we access information. Era 5.0, has a technological concept where data and information is collected by the Internet of things (IoT) which is transformed by Artificial Intelligence (AI) into something that can help people live a better life. In the context of chemistry learning, one of the approaches that can be developed is digital entertainment-based learning media. This preliminary study aims to dig deeper into the potential and benefits of digital entertainment chemistry-based learning media in the context of Era 5.0. The method used was a survey involving 177 high school students by providing 30 open and closed question items via Google Forms online. Based on the survey results, it is known that the use of podcasts as digital entertainment-based learning media is considered suitable and has many positive impacts, as long as it is properly implemented and receives adequate support from the school and the government.